Role of Theme-Rheme Analysis in Developing Academic Literacy Skills in Senior High School Students in Pringsewu - Tiara Noviarini (ELT-Lectura, 2025)
This study aims to explore the implementation of Theme-Rheme in developing the writing ability of second-grade students at SMA Muhammadiyah Pringsewu. Theme-Rheme, as part of systemic functional theory, provides a framework for analyzing the structure and flow of information within sentences. The research method used is qualitative descriptive with a text analysis approach to students' writings. The results show that understanding and applying Theme-Rheme significantly help students in organizing ideas and enhancing the cohesion and coherence of their writing. Additionally, this technique encourages students to be more critical in constructing arguments and developing well-structured paragraphs. These findings suggest that Theme-Rheme-based learning can be an effective strategy in improving students' writing abilities at the secondary school level.